Extended cohesive zone model for simulation of solder/IMC interface cyclic damage process in pb-free solder interconnects - Yamin, A.F.M.; Shaffiar, N.M.; Loh, W.K.; Tamin, M.N. (2012)
The current formulation of stress- and energy-based cohesive zone model (CZM) is extended to account for load reversals. Cyclic degradation of solder/IMC interface properties, namely penalty stiffness, strengths and critical energy release rates follows power-law functions of fatigue cycles. Performance of the extended CZM is examined using finite element (FE) simulation of a single Sn-4Ag-0.5Cu (SAC405) solder interconnect specimen. Strain ratedependent response of the solder is represented by unified inelastic strain equations (Anand’s model) with optimized model parameters for SAC405 solders. The 3D FE model of the specimen is subjected to cyclic relative displacement (Δδ = 0.003 mm, R = 0) so as to induce shear-dominant fatigue loading. Results show that interface crack initiated at the leading edge of the solder/IMC interface on the tool side of the assembly after 22 cycles have elapsed. Bending stress component induced by the solder stand-off height dominates the interface damage process. A straight interface crack front is predicted indicating the relatively brittle nature of the SAC405/Cu6Sn5 interface. The extended formulation of the CZM to account for load reversals has demonstrated the ability to describe the progressive solder/IMC interface damage process consistent with the mechanics of relatively brittle interface fracture.